Gut microbiome signatures and host colonization with multidrug-resistant bacteria. Issue 9 (September 2022) - Isles, Nicole S.; Mu, Andre; Kwong, Jason C.; Howden, Benjamin P.; Stinear, Timothy P.
Abstract : The human gut is host to a diverse range of microorganisms that offer protection against colonization by multidrug-resistant bacteria. Antibiotic use, medications, health conditions, and lifestyle factors can alter the composition of the gut microbiota in such a way that results in loss of colonization resistance and increased susceptibility to invading pathogenic antibiotic-resistant bacteria. Therapeutics aiming to restore a diverse and protective microbiome are fast advancing. In this review, we focus on the compositional changes within the gut microbiome that are associated with colonization resistance and discuss their use as potential targets for therapeutics or diagnostics. Highlights: Multi-omic approaches aid the identification of microbial and metabolic signatures in the gut ecosystem that are associated with colonization resistance against multidrug-resistant organisms. Microbial signatures present as potential biomarkers for diagnostic and therapeutic tools, including predictive models for the identification of the risk of MDRO acquisition and the anticipated efficacy of treatments, such as FMT or phage therapy, in decolonizing MDROs from the gut.